If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7u + -2u = 3u + 22 Combine like terms: 7u + -2u = 5u 5u = 3u + 22 Reorder the terms: 5u = 22 + 3u Solving 5u = 22 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 5u + -3u = 22 + 3u + -3u Combine like terms: 5u + -3u = 2u 2u = 22 + 3u + -3u Combine like terms: 3u + -3u = 0 2u = 22 + 0 2u = 22 Divide each side by '2'. u = 11 Simplifying u = 11
| 2x^2+31x+110=0 | | -4.5c=-27 | | 4x^2+27x+-12=0 | | X+11+x=43 | | 2.4z=-24 | | 13d+25=8d | | 1.5b-16=8 | | 99+6u=-3u | | 0.03(x-40)+0.9(x+10)=45 | | -4x-10x=25 | | -(-6)=6x | | 12-9w=75 | | -64=-15m-4 | | 9x=2x+14 | | 8x+63+20+x=-61 | | -11=61-6q | | 3(d-1)+4=-2d | | 90=10p-90 | | 5+4x-7-3x=-2 | | 7y=2y-15 | | h=(-16t)(-16t)+541 | | -8-3y=25 | | 5+4n=29 | | -6z=.625 | | 2xm+x+2xm+x=18 | | 2=(-16t)(-16t)+541 | | 93-4y=5y+12 | | 4x+10-2x=6x+3 | | 2.4(m-3)+3.8=8.2 | | -6x+42=48 | | .2a=3 | | .2a=-3 |